Trideset let literarne nagrade večernica (University of Maribor Press, 2026)
Thirty Years of the Večernica Literary Award. The scholarly monograph examines the significance of the Večernica Award, Slovenia’s most important award in the field of children’s and young adult (YA) literature, bestowed annually at the Oko Besede (Eye of the Word) festival in Murska Sobota. It considers all the nominated and award-winning works that have, over the thirty years of the award (1997–2026), contributed to the canonisation, promotion and development of original literary works in Slovenia with diverse themes, literary genres and formats. Nominated and winning works for the Večernica Award are presented in sixteen chapters, organised according to literary genre, literary space, literary time, narrator, structure, and themes and motifs. The chapters also consider multimodality as a distinct book form; connections with other media (music, dance) and fields (ethics); the use of language in children’s and YA literature (including translation); and didactic value, including the incorporation of nominated and award-winning works into school curricula.